Intergenerational correlation of labour market outcomes - Kalb, G; Herault, N (My University, 2014)
This paper contributes to the relatively limited literature on the correlation of labor market outcomes of parents and their children. This literature is relevant to the larger literature on intergenerational income mobility since correlation in intergenerational labor market outcomes is one of the potential factors contributing to the intergenerational correlation of permanent incomes. In this paper, we consider the time spent in unemployment by both sons and daughters, while accounting for the potential endogeneity of education. Using the Household, Income and Labour Dynamics in Australia data, we find evidence of a positive correlation of labor market outcomes between fathers and sons and, to a lesser extent, between mothers and daughters. In addition, the results reveal a significant relationship between parents’ and children’s education levels, indicating that there is an indirect association of parental education with their children’s labor market outcomes through education.
Keywords: Employment -- Labour market outcomes; Employment; Education and Training -- Background; Intergenerational Transfer -- Education; Intergenerational transfer; Labour market; Learning, education and training; Education and Training; Intergenerational Transfer; Employment; Education; Labour market outcomes; Background; Learning, education and training; Intergenerational transfer; Employment and unemployment